Emotion Recognition and Theory of Mind in Autism Spectrum Disorder and ADHD - Riehl, Hannah. (Tufts University. Tisch Library., 2020)
Thesis (M.A.)--Tufts University, 2020.; Submitted to the Dept. of Child Development.; Advisor: Eileen Crehan.; Committee: Martha Pott, and Amanda Cremone-Caira.; Keyword: Psychology.